2016
DOI: 10.1371/journal.pone.0146148
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improved Flow-Mediated Outward Arterial Remodeling in Ovariectomized Rats with Hypertrophic Effect at High Dose

Abstract: ObjectivesChronic increases in blood flow in resistance arteries induce outward remodeling associated with increased wall thickness and endothelium-mediated dilatation. This remodeling is essential for collateral arteries growth following occlusion of a large artery. As estrogens have a major role in this remodeling, we hypothesized that resveratrol, described as possessing phytoestrogen properties, could improve remodeling in ovariectomized rats.MethodsBlood flow was increased in vivo in mesenteric arteries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…This remodeling involves an early inflammatory phase allowing cell growth and reorganization in the arterial wall ( Caillon et al, 2016 ) and a dilatory phase involving NO, prostaglandins and CO production ( Dumont et al, 2007 ; Belin de Chantemèle et al, 2010 ; Freidja et al, 2011 ). Noteworthy, flow-mediated remodeling is absent in ovariectomized rats and mice and in Esr1 -/- mice ( Tarhouni et al, 2013 ) whereas this remodeling is preserved in ovariectomized rats treated with E2 ( Tarhouni et al, 2014b ) or resveratrol ( Petit et al, 2016 ). More recently, we have shown that this remodeling requires activation of AF2 and is independent on membrane-located ERα ( Guivarc’h et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This remodeling involves an early inflammatory phase allowing cell growth and reorganization in the arterial wall ( Caillon et al, 2016 ) and a dilatory phase involving NO, prostaglandins and CO production ( Dumont et al, 2007 ; Belin de Chantemèle et al, 2010 ; Freidja et al, 2011 ). Noteworthy, flow-mediated remodeling is absent in ovariectomized rats and mice and in Esr1 -/- mice ( Tarhouni et al, 2013 ) whereas this remodeling is preserved in ovariectomized rats treated with E2 ( Tarhouni et al, 2014b ) or resveratrol ( Petit et al, 2016 ). More recently, we have shown that this remodeling requires activation of AF2 and is independent on membrane-located ERα ( Guivarc’h et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has been shown to prevent arterial remodelling and stiffening in both animal and clinical studies. In rats, both low-dose and high-dose resveratrol treatments improve flow-mediated outward remodelling [80]. A long-term low-dose dietary resveratrol supplement reduces arterial stiffness (measured by the aortic pulse wave velocity) in rats [81].…”
Section: Prevention Of Arterial Stiffeningmentioning
confidence: 99%
“…For that reason, this potent molecule (even with a short half-life) also would be highly beneficial as an adjuvant therapy for diabetes. Additionally, under in vitro [ 107 , 108 ] and in vivo [ 109 , 110 , 111 ] experimental conditions that mimic human diabetes, resveratrol has been shown to have a potential benefit in several multi-target mechanisms for diabetic complications, as presented below.…”
Section: Potential Of Natural Products With Antioxidant Effects Fomentioning
confidence: 99%